Trilock Brick : Inovasi Desain Batako Bentuk Segitiga dengan Sistem Interlock - Ningtiyas, Ubbidah Agus (Jurnal Proyek Teknik Sipil, 2024)
As the construction industry in Indonesia continues to grow, it has significantly impacted the demand for building materials, particularly in the construction sector. One such material is "batako," which is used as a wall filler, along with cement as a bonding material (grout). Therefore, there is a need for a solution that provides easier workability during installation and is cost-effective. The objective of this research is to innovate and analyze the design of triangular-shaped batako with an interlocking system on each side. The methodology used involves experimental testing in a laboratory and follows the Indonesian National Standard (SNI) 03-0349-1989. The process includes material testing, specimen production, compressive strength testing, absorption testing, and a cost comparison analysis. The research resulted in the development of "trilock brick," a triangular-shaped batako measuring 36 cm in length and 9 cm in thickness. The average compressive strength at 28 days was 9,487 MPa, with an average water absorption rate of 5.344%. The installation cost per 1 m2 was Rp. 76,802, with a grout thickness of 0,5 cm. This research demonstrates that this innovation possesses compressive strength and water absorption values comparable to conventional batako. Additionally, trilock brick offers economic advantages with a cost difference of up to 13% compared to conventional batako requirements.